ANALYSIS OF INNOVATIVE ACTIVITIES OF COMPANIES IN DEVELOPED COUNTRIES - Shayakubov Shakhzod Shakabilovich (Journals Park Publishing, 2022)
This article describes the innovative products offered to the world markets by large companies operating in developed countries, as a result of which companies and investments in countries, and provides relevant analysis and recommendations on this topic.
Keywords: innovative activity, innovative product; investment